The Fosfomycin Resistance Gene fosB3 Is Located on a Transferable, Extrachromosomal Circular Intermediate in Clinical Enterococcus faecium Isolates - Xu, Xiaogang; Chen, Chunhui; Lin, Dongfang; Guo, Qinglan; Hu, Fupin; Zhu, Demei; Li, Guanghui; Wang, Minggui (PLOS ONE, 2013)
Some VanM-type vancomycin-resistant Enterococcus faecium isolates from China are also resistant to fosfomycin. To investigate the mechanism of fosfomycin resistance in these clinical isolates, antimicrobial susceptibility testing, filter-mating, Illumina/Solexa sequencing, inverse PCR and fosfomycin resistance gene cloning were performed. Three E. faecium clinical isolates were highly resistant to fosfomycin and vancomycin with minimal inhibitory concentrations (MICs) >1024 µg/ml and >256 µg/ml, respectively. The fosfomycin and vancomycin resistance of these strains could be co-transferred by conjugation. They carried a fosfomycin resistance gene fosB encoding a protein differing by one or two amino acids from FosB, which is encoded on staphylococcal plasmids. Accordingly, the gene was designated fosB3. The fosB3 gene was cloned into pMD19-T, and transformed into E. coli DH5α. The fosfomycin MIC for transformants with fosB3 was 750-fold higher than transformants without fosB3. The fosB3 gene could be transferred by an extrachromosomal circular intermediate. The results indicate that the fosB3 gene is transferable, can mediate high level fosfomycin resistance in both Gram-positive and Gram-negative bacteria, and can be located on a circular intermediate.